2004
DOI: 10.1101/gad.1220104
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray structure of the papillomavirus helicase in complex with its molecular matchmaker E2

Abstract: DNA replication of the papillomaviruses is specified by cooperative binding of two proteins to the ori site: the enhancer E2 and the viral initiator E1, a distant member of the AAA+ family of proteins. Formation of this prereplication complex is an essential step toward the construction of a functional, multimeric E1 helicase and DNA melting. To understand how E2 interacts with E1 to regulate this process, we have solved the X-ray structure of a complex containing the HPV18 E2 activation domain bound to the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
173
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(179 citation statements)
references
References 60 publications
5
173
0
1
Order By: Relevance
“…3B, lanes [7][8][9][10][11][12][13][14][15][16][17][18]. Two other substitutions with long aliphatic side chains, H513M and H513L, also displayed helicase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B, lanes [7][8][9][10][11][12][13][14][15][16][17][18]. Two other substitutions with long aliphatic side chains, H513M and H513L, also displayed helicase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8) (11,(17)(18)(19). However, some AAA ϩ hexameric protein machines, e.g., NSF and p97 for membrane fusion (20)(21)(22), do not possess a similar ␤-hairpin structure.…”
Section: Discussionmentioning
confidence: 99%
“…A prime candidate for the interaction with the TA bp is a ␤-hairpin structure, which is highly conserved in E1 and other papovavirus initiator proteins (1,18). Our previous studies have demonstrated that H507 at the tip of this ␤-hairpin is required for DT formation and for template melting (28).…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of E1 and T-Ag have provided important information about the domain structure, how these proteins oligomerize, and how they bind and hydrolyze nucleotides (1,10,13,18). Biochemical analysis has demonstrated that one particular form of E1, a double trimer (DT), generates permanganate reactivity in the ori in the presence of ADP, indicating that the DT provides template melting activity (28).…”
mentioning
confidence: 99%
“…The full-length E2 protein is a sequence-specific DNAbinding protein implicated in the control of viral DNA replication (Stenlund 2003;Abbate et al 2004), transcription (Hou et al 2002), cell cycle progression (Hwang et al 1993), apoptosis (Blachon et al 2005), senescence (Goodwin and DiMaio 2001), and viral genome maintenance and segregation (Abroi et al 2004;Botchan 2004;McBride et al 2004;Van Tine et al 2004;You et al 2004). Like many cellular transcription factors with different functional modules, E2 contains a C-terminal DNA-binding domain linked to the N-terminal transactivation domain by a flexible hinge.…”
mentioning
confidence: 99%